ANALISIS PERMINTAAN TELUR DI KABUPATEN SLEMAN - Ani Suryani (Jurnal Agrisep)
The objectives of this research are to determine factors affecting egg demand during the period of 1991 to 2007, and to examine the prospect of egg as inferior, normal or superior commodity in Sleman District. The research location is determined purposively. The method used in this research is descriptive analysis with time series data (1991-2007). This study uses demand function approach by applying multiple regression model estimated using OLS (ordinary least square).The result of estimation shows that the partial demand of egg in Sleman District is caused by the price of fish, rice, population, income per capita and economical crisis. The elasticity of egg demand toward price elasticity is inelastic in the scale of 0.59. Egg in this district is categorized as a normal goo. This conclusion is based on finding that income per capita is positively correlated toward egg demand with the coefficient of regressionof 0.36. Egg consumption at Sleman district from time to time tends to increase coinciding with the growth of income per capita.